Experience and kerygma a critical study of Jose M. De Mesa's contextual theological model - Canlas, Reshley Ramon M. (Giraffe Books, 2008)
"The main task of this book is to evaluate the model of Dr. Jose M. de Mesa's model of doing contextual theology whether this is consistent with the experience and kerygma and of the Church."--Introduction.